PERIODE DAN FASE-FASE PENDIDIKAN ISLAM: ANALISIS KOMPREHENSIF DALAM PEMBENTUKAN KARAKTER INDIVIDU - Wahyudi Wahyudi; Fajar Sukma Nashrullah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The process of Islamic education is a lifelong journey that spans from the prenatal stage, prior to birth, all the way to adulthood. In Islam, education transcends mere academic learning; it encompasses character development, spirituality, and the emotional and social preparedness of individuals. This article meticulously explores the various phases of Islamic education, starting with prenatal education, which includes considerations of partner selection and pregnancy, and continuing with postnatal education that addresses the growth and development of infants, children, adolescents, and adults. Furthermore, it examines how education contributes to the formation of individuals who possess both intellectual and moral equilibrium. Employing an analytical and reflective methodology, this study underscores the significance of Islamic education in contemporary society and the obstacles it encounters in the context of globalization. A more profound comprehension of Islamic education aims to offer valuable insights for parents, educators, and the community in nurturing a generation characterized by strong moral integrity.